Differential In vitro and In vivo Behavior of Mouse Ascorbate/Fe3+ and Diamide Oxidized Erythrocytes. Issue 6 (December 2001) - Lotero, L. Alfredo; Jordán, José A.; Olmos, Gemma; Alvarez, F. Javier; Tejedor, M. Cristina; Diez, José C.
Abstract : Chemical oxidation of mouse erythrocytes has been carried out using two different oxidizing systems namely: Diamide and Ascorbate/Fe 3+ together with different concentrations of the oxidant. These oxidation treatments produced different extents of modification in membrane proteins as was observed by electrophoretic analyses that showed a possible formation of high molecular weight aggregates. Lipid peroxidation was also observed as the result of these chemical treatments. The action of these two oxidation treatments produced different extents of lipid peroxidation in which the effect Ascorbate/Fe 3+ reached higher values than that shown by diamide treatments. To study the resulting in vitro behavior of such oxidized erythrocytes, we have evaluated the recognition of oxidized erythrocytes by peritoneal macrophages. In the conditions used, diamide oxidized erythrocytes were more highly recognized by macrophages than Ascorbate/Fe 3+ treated erythrocytes. However, in both cases an influence of serum factors in the recognition process can be inferred. Additionally, we have correlated on one side the action of different oxidation systems on mouse erythrocytes with different in vivo behavior and organ uptake of the oxidized erythrocytes. On the other side, differential targeting of oxidized erythrocytes to a liver or spleen was observed on dependence of the oxidant used.